Knowledge and awareness assessment of dental students about malignant melanoma - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Background: Epidemiological studies have shown an increased tendency to malignant melanoma worldwide. Dentistry students need comprehensive up-to-date information about malignant melanoma to give their patients correct advice. The purpose of this study is to assess 3rd, 4th, and 5th grade students' level of knowledge and awareness about malignant melanoma. Materials and Methods: In our study, a questionnaire consisting of 11 questions was applied to a total of 229 students, 93 3rd grade, 64 4th grade, and 72 5th grade students who were educated at Marmara University, Faculty of Dentistry. In this survey, students' level of knowledge and awareness was examined. Results: A total of 75 (32.75%) male and 154 (67.25%) female students were included in the study. There was a statistically significant difference between grades in terms of participation rate to the statement Oral melanomas are more aggressive than skin involvement (P = 0.000). Participation rate of 3rd grades (30.11%) was significantly lower than 4th grades (45.31%) and 5th grades (48.61%) (P1 = 0.004; P2=, 0.000). There was a statistically significant difference between grades in terms of participation rate to the statement Oral melanoma lesions are usually asymptomatic (P = 0,000). Participation rate of 3rd grades (15.05%) was significantly lower than 4th grades (39.06%) and 5th grades (58.33%) (P1 = 0.002; P2 = 0.000). Participation rate of 4th grades was significantly lower than 5th grades (P = 0.033). Conclusion: Providing the necessary training on malignant melanoma will improve the knowledge and awareness of dentistry students.
Keywords: Awareness; malignant melanoma; oral cancer; ORAL MUCOSAL MELANOMA; MEDICAL-STUDENTS; SKIN-CANCER; BEHAVIORS; CAVITY